La nidificación de la Harpía (Harpia harpyja) en Argentina - Chebez, Juan Carlos (1990)
Nesting of the Harpy Eagle in Misiones, Argentina. The presence of Harpía harpyja is actualized in the country confirming as a nidifying species due to three nests which were found in the province of Misiones. Nests are described revealing the first details about diet of this eagle in Argentina.